2018
DOI: 10.5296/jbls.v9i1.12222
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of Round Sardinella (Sardinella Aurita) (Valenciennes, 1847) in Senegalese Coastal Waters

Abstract: In this study, a total of 1068 specimens Sardinella aurita of which 553 females and 515 males were examined. The objectif of this study was to determine the reproductive parameters of Sardinella aurita. The sex ratio was significantly in favor of females (55%). The size at first sexual maturity was estimated at 18.9 cm for females and 18.0 cm for males. The monthly variation of sexual maturity stages and gonado-somatic index (GSI) allowed to locate the reproduction periods from February to June and from Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…As in the present study, other authors had observed that females of S. aurita slightly outnumber males or are approximately equal to males in Mauritanian waters (Wagué & M'Bodj, 2002; Chesheva, 2006). A slight predominance of females has also been observed in South Morocco (Baali et al ., 2017), Senegal (Boëly, 1982; Ndiaye et al ., 2018; Baldé et al ., 2019 b ) and in the Mediterranean Sea (Tsikliras & Antonopoulou, 2006; Mustac & Sinovcic, 2012). Nevertheless, a significant unbalanced sex-ratio has been described in the Mediterranean Sea (Navarro, 1932; Dahel et al ., 2016) and in the SW Atlantic (Gassman et al ., 2008; Tagliafico et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in the present study, other authors had observed that females of S. aurita slightly outnumber males or are approximately equal to males in Mauritanian waters (Wagué & M'Bodj, 2002; Chesheva, 2006). A slight predominance of females has also been observed in South Morocco (Baali et al ., 2017), Senegal (Boëly, 1982; Ndiaye et al ., 2018; Baldé et al ., 2019 b ) and in the Mediterranean Sea (Tsikliras & Antonopoulou, 2006; Mustac & Sinovcic, 2012). Nevertheless, a significant unbalanced sex-ratio has been described in the Mediterranean Sea (Navarro, 1932; Dahel et al ., 2016) and in the SW Atlantic (Gassman et al ., 2008; Tagliafico et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The lengths at first maturity (LFMs) estimated in the present study (~24 cm TL) are similar to results obtained by other authors for the Mauritanian round sardinella (ter Hofstede et al ., 2007; Ndiaye et al ., 2018). The species reaches its maturity at bigger sizes both in NW Africa (including South Morocco) (Baali et al ., 2015, 2017; Amenzoui & Baali, 2018), compared with the LFM estimated southwards (Castro et al ., 2017), and also in the Mediterranean Sea (Tsikliras & Antonopoulou, 2006) and in SW Atlantic waters (Gassman et al ., 2008; Tagliafico et al ., 2008), probably due to the influence of the powerful upwelling in the area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall sex ratio obtained for the round sardinella in the Canary Islands resulted in a significant unbalance towards males, in contrast with NW African waters where balanced sex ratios have been observed off Mauritania (Wagué & M'Bodj, 2002; Chesheva, 2006), or where females predominated in landings off South Morocco (Baali et al ., 2017), Mauritania (Jurado-Ruzafa et al ., 2020) and Senegal (Boëly, 1982; Ndiaye et al ., 2018; Baldé et al ., 2019). Unbalance to females is also reported in the Mediterranean Sea (Tsikliras & Antonopoulou, 2006; Mustac & Sinovcic, 2012).…”
Section: Discussionmentioning
confidence: 99%